Pain Modulation in WAG/Rij Epileptic Rats (A Genetic Model of Absence Epilepsy): Effects of Biological and Pharmacological Histone Deacetylase Inhibitors - De Caro, Carmen; Di Cesare Mannelli, Lorenzo; Branca, Jacopo Junio Valerio; Micheli, Laura; Citraro, Rita; Russo, Emilio; De Sarro, Giovambattista; Ghelardini, Carla; Calignano, Antonio; Russo, Roberto (Frontiers in Pharmacology, 2020)
Epigenetic mechanisms are involved in epilepsy and chronic pain development. About that, we studied the effects of the natural histone deacetylase (HDAC) inhibitor sodium butyrate (BUT) in comparison with valproic acid (VPA) in a validated genetic model of generalized absence epilepsy and epileptogenesis. WAG/Rij rats were treated with BUT (30 mg/kg), VPA (300 mg/kg) and their combination (BUT+VPA) daily per os for 6 months. Rats were subjected at Randall-Selitto, von Frey, hot plate and tail flick tests after 1, 3 and 6 months of treatment to evaluate hypersensitivity to noxious and non noxious stimuli. Moreover, PPAR-gamma (G3335 1 mg/kg), GABA-B (CGP35348 80 mg/kg) and opioid (naloxone 1 mg/kg) receptor antagonists were administrated to investigate the possible mechanisms involved in analgesic activity. The expression of NF-kB, glutathione reductase and protein oxidation (carbonylation) were also evaluated by western blot analysis. WAG/Rij rats showed an altered pain threshold throughout the study (P<0.001). BUT and BUT+VPA treatment reduced hypersensitivity (P<0.01). VPA was significantly effective only after 1 month (P<0.01). All the three receptors are involved in BUT+VPA effects (P<0.001). BUT and BUT+VPA decreased the expression of NF-kB and enhanced glutathione reductase (P<0.01); protein oxidation (carbonylation) was reduced (P<0.01). No effect was reported with VPA. In conclusion BUT, alone or in co-administration with VPA, is a valuable candidate for managing the epilepsy-related persistent pain.